Azacitidine and prophylactic donor lymphocyte infusions after hematopoietic stem cell transplantation for pediatric high-risk acute myeloid leukemia. (4th November 2020) - Huschart, Emily; Miller, Holly; Salzberg, Dana; Campbell, Courtney; Beebe, Kristen; Schwalbach, Charlotte; Magee, Kyrie; Adams, Roberta H.; Ngwube, Alexander
Abstract: Post-hematopoietic stem cell transplantation (HSCT) maintenance therapy using azacitidine and prophylactic donor lymphocyte infusions (DLI) was implemented for high-risk acute myeloid leukemia. Azacitidine was started on day +60 as a 5 day course every 28 days for 6 cycles. DLI was given every 6 weeks for 3 doses starting after day +120. Ten patients were treated on this protocol. With a 90% one-year disease free survival, we report this post-HSCT maintenance therapy is feasible, safe, and well tolerated.